Pentraxin-3 as a poor marker of fibrosis in metabolic dysfunction-associated steatotic liver disease among older adults: findings from the PolSenior2 substudy - Owczarek, Aleksander Jerzy; Musialik, Joanna; Stefański, Adrian; Mossakowska, Małgorzata; Zięba, Katarzyna; Więcek, Andrzej; Chudek, Jerzy; Olszanecka-Glinianowicz, Magdalena (Frontiers in Medicine, 2025)
IntroductionThe study aimed to assess the relationship between plasma pentraxin 3 (PTX-3) levels and the potential diagnosis of fibrosis in metabolic dysfunction-associated steatohepatitis (MASH) in older adults. This was assessed using the Fibrosis-4 index (FIB-4), NAFLD fibrosis score (NFS), and Hepamet fibrosis score (HFS).Materials and methodsThe subanalysis included 2,397 older adults (aged 60 years and older) from the population-based PolSenior2 study, all of whom had risk factors for metabolic dysfunction-associated steatotic liver disease (MASLD) and underwent PTX-3 assessment. The participants were divided into two subgroups according to the FIB-4 values (≤2.67 and > 2.67), three subgroups according to the NFS values (< −1.455, −1.455, and 0.675, and > 0.675), and three subgroups according to the HFS values (< 0.12, 0.12 and 0.47 and > 0.47).ResultsThe empirical cutoff points for PTX-3 levels as a potential marker of liver fibrosis were assessed separately for women and men. In women, the cutoff points for PTX-3 levels based on ROC curve analyses ranged from 1.96 to 2.30 ng/mL (an AUC ranging from 0.596 to 0.643, sensitivity between 39.1 and 61.7%, and specificity between 56.1 and 79.6%). In men, a significant cutoff point was established for FIB-4 (an AUC of 0.549, sensitivity of 39.4%, and specificity of 69.6%). Overall, the accuracy was poor.ConclusionOur study suggests that plasma PTX-3 levels are not sensitive enough to be used as a non-specific marker of liver fibrosis in older adults.